Engineering drawing & design - Madsen, David A. (Drafting and design series, 2007)
For more than twenty years, customers have relied on Engineering Drawing and Design for its easy-to-read, A-to-Z coverage of drafting and design instruction that complies with industry standards. The fourth edition continues its tradition of excellence with a multitude of actual quality industry drawings demonstrating content coverage, and the addition of new problems to the hundreds already on-hand for real world, practical application. The engineering design process featured in this revision contains all-new material following an actual product design from concept through manufacturing, and a multitude of new design problems for challenging applications or for use as team projects. Other enhancements include updated coverage of Civil Drafting, 3D CADD, solid modeling, parametric applications, and more.